Sistematización del proceso de diseño y fabricación de mecanismos recreativos mediante metodología DFMA - Diseño para fabricación y ensamble – para la empresa Tablecortes S.A.S. (2024)
The design and manufacture process of leisure mechanisms supported by DFMA methodology does not exist at Tablecortes S.A.S. This proposal presents the project to organize the design and manufacture process of entertainment mechanisms for children and adults, using the DFMA methodology - Design for Manufacture and Assembly.